EFEKTIVITAS PROGRAM KELUARGA HARAPAN TERHADAP PRODUKTIVITAS DAN DAMPAKNYA PADA KESEJAHTERAAN MASYARAKAT DI KABUPATEN PIDIE DENGAN KEBIJAKAN PEMERINTAH SEBAGAI VARIABEL PEMODERASI - Ali, Muhammad (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2026)
The purpose of this study was to examine the effectiveness of the Family Hope Program (PKH) on productivity and its impact on community welfare in Pidie Regency, with government policy as a moderating variable. A sample size of 320 individuals from a population of 36,230 was selected using a Krejcie table at a significance level of 0.05 and a 95% confidence level. Probability sampling was used, followed by proportionate stratified random sampling. Data were collected using a questionnaire, analyzed using Structural Equation Modeling (SEM) and processed with AMOS software version 24.0. The results indicate that the effectiveness of the Family Hope Program significantly impacts the welfare of PKH recipients in Pidie Regency, both directly and through the moderating variables of productivity and policy. The results also indicate that the direct effect is greater than the indirect effect between the variables studied.